PENDIDIKAN KARAKTER ANAK MELALUI KETERAMPILAN LITERASI DENGAN PENDEKATAN SIX E’S - Ulfasari, Nia; Azizatul Khairi (Jurnal Pendidikan Sepanjang Hayat, 2024)
This research aims to analyze children's character education through literacy skills by applying the Six E's approach. The study uses qualitative methods, including unstructured interviews and observations in elementary schools in Bengkulu City. Findings reveal that independent reading literacy for 15 minutes has several weaknesses, such as limited time, unengaging references, and lack of guidance. The study highlights the importance of developing holistic literacy skills, including comprehension, analysis, and text evaluation. The Six E's approach is expected to enhance literacy skills and shape children's character through meaningful text interactions and critical activities. Therefore, it serves as a useful guide for teachers to improve children's literacy quality